Diels–Alder reaction between 1, 3, 3-trisubstituted-2-vinylcyclohexenes and quinones under exceptionally mild conditions: a concise entry to the cassane-type furanoditerpenoid skeleton. Issue 32 (10th August 2016) - Tzouma, Eirini; Mavridis, Ioannis; Vidali, Veroniki P.; Pitsinos, Emmanuel N.
Graphical abstract: Highlights: Cassane-type furanoditerpenes encompass a large number of natural products. A strategy towards this motif based on a demanding DA reaction is proposed. Hexafluoroisopropanol allows this reaction to proceed under normal pressure. A concise and enantioselective construction of the required diene is reported. The feasibility of the proposed strategy has been demonstrated. Abstract: Extremely mild (no metal Lewis acid catalyst, ambient temperature) and experimentally simple (no high-pressure apparatus needed) conditions were established for the Diels–Alder reaction between sterically demanding 1, 3, 3-trisubstituted-2-vinylcyclohexenes and non-symmetrically substituted quinones. This allowed for the successful implementation of a highly convergent strategy to the cassane-type furanoditerpenoid skeleton.